Injuries among adolescents in Greenland: behavioural and socio-economic correlates among a nationally representative sample - Jansen, Louis; Bärnighausen, Till; Wilson, Michael (PeerJ, 2020)
Background Injuries are among the most important threats to adolescent health, making examination of the patterns and risk factors a critical area of research. There exists a paucity of information on the health and injury experience of school-attending adolescents in Greenland. Consenting Greenlandic schoolchildren (n = 2,254) aged 9-19 years were included in the Health Behavior in School-Aged Children study 2005/2006. The aim of this study was to examine the socio-economic and behavioural correlates that were associated with injury occurrence among school-attending Greenlandic adolescents. Methods This study made use of two multinomial regression models to examine injury occurrence regarding potential influencing factors such as physical activity, risk behaviours, bullying and family socio-economic status (SES). Results Those self-reporting 1-2 injuries within the recall period were more likely to be male (OR = 1.70; CI [1.39-2.09]), involved in physical fighting (OR = 1.82; CI [1.33-2.47]), bullied (OR = 1.81; CI [1.47-2.24]) and participated in bullying others (OR = 1.53; CI [1.25-1.89]). Those reporting three or more injuries were again mostly male (OR = 2.13; CI [1.44-3.14]), involved in physical fighting at higher rates (OR = 4.47; CI [2.86-7.01]), bullied more often (OR = 2.43; CI [1.65-3.57]) and were more likely to bully others (OR = 1.67; CI [1.13-2.45]). Living without a mother proved to be significantly correlated with suffering 3 or more injuries during the recall period (OR = 1.63; CI [1.05-2.52]). The study results support the idea that factors that were found to be associated with injury occurrence, such as bullying and aggressive behaviour, should be taken into account when conducting future research on the nature of injuries among Greenlandic adolescents. More research on this topic is needed to identify factors that might modify the associations between injuries and adolescent behaviour and SES.